Multilevel multistate hybrid voltage regulator - Abdulslam, Abdullah Amgad Abdulaziz (AUC Knowledge Fountain, 2015)
In this work, a new set of voltage regulators as well as some controlling methods and schemes are proposed. While normal switched capacitor voltage regulators are easy integrable, they are suffering from charge sharing losses as well as fast degradation of efficiency when deviating from target operation point. On the other hand, conventional buck converters use bulky magnetic components that introduce challenges to integrate them on chip. The new set of voltage regulators covers the gap between inductor-based and capacitor-based voltage regulators by taking the advantages of both of them while avoiding or minimizing their disadvantages. The voltage regulator device consists of a switched capacitor circuit that is periodically switching its output between different voltage levels followed by a low pass filter to give a regulated output voltage. The voltage regulator is capable of converting an input voltage to a wide range of output voltage with a high efficiency that is roughly constant over the whole operation range. By switching between adjacent voltage levels, the voltage drop on the inductor is limited allowing for the use of smaller inductor sizes while maintaining the same performance. The general concept of the proposed voltage regulator as well as some operating conditions and techniques are explained. A phase interleaving technique to operate the multilevel multistate voltage regulator has been proposed. In this technique, the phases of two or more voltage levels are interleaved which enhances the effective switching frequency of the charge transferring components. This results in a further boost in the proposed regulator's performance. A 4-level 4-state hybrid voltage regulator has been introduced as an application on the proposed concepts and techniques. It shows better performance compared to both integrated inductor-based and capacitor-based voltage regulators. The results prove that the proposed set of voltage regulators offers a potential move towards easing the integration of voltage regulators on chip with a performance that approaches that of off-chip voltage regulators.